2019
DOI: 10.1002/ceat.201800646
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Kinetics for Batch Cooling Crystallization by Focused‐Beam Reflectance Measurements

Abstract: Numerical simulation of the seeded batch cooling crystallization process of active pharmaceutical ingredients was performed. Crystal size distribution was observed by focused-beam reflectance measurements and concentration by simultaneous Fourier transform infrared spectroscopy. First, kinetic parameters were estimated. Nucleation rate coefficient and order were estimated from the linear regression equation between cooling rate and metastable zone width. The remaining parameters were estimated from the evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Here, R is the gas constant, T is the absolute temperature, Δ T is the super‐cooling, σ is the relative supersaturation, k b0 , E b , and b are the nucleation rate constant, the activation energy, and the order, respectively, and k g0 , E g , and g are the growth rate constant, the activation energy, and the order, respectively. The kinetic parameters in the above equations were estimated in the previous study and are listed in Tab. .…”
Section: Methodsmentioning
confidence: 99%
“…Here, R is the gas constant, T is the absolute temperature, Δ T is the super‐cooling, σ is the relative supersaturation, k b0 , E b , and b are the nucleation rate constant, the activation energy, and the order, respectively, and k g0 , E g , and g are the growth rate constant, the activation energy, and the order, respectively. The kinetic parameters in the above equations were estimated in the previous study and are listed in Tab. .…”
Section: Methodsmentioning
confidence: 99%
“…Each element of the shape transformation matrix S corresponds with the ratio of the probability event of each chord length range in the sample space of the domains of five independent variables and can be computed with Monte Carlo analysis . For example, ( S ) ij corresponds with the probability that the chord length defined by five independent variables, the values of which are uniformly random within the domain of the j ‐th bin in CSD, is present within the range of the i‐ th bin in CLD.…”
Section: Methodsmentioning
confidence: 99%
“…In previous work , the algorithm of the computation of the mapping matrix which can afford to take into account the change in crystal shape was described. In this study, the suspension of L ‐arginine (Arg) in water was used.…”
Section: Introductionmentioning
confidence: 99%
“…In any case, previous studies have shown that sonication during crystallization can affect the induction time and metastable zone width, the mechanism and rate of nucleation, but also the kinetics of crystal growth [5][6][7][8][9]. Sonication also increases the repeatability which is one of its key advantages in comparison to conventional crystallization.…”
Section: Introductionmentioning
confidence: 99%